Влияние метаболитов микроорганизмов, выделенных из многолетнемерзлых пород Западной и Восточной Сибири, на пролиферативную активность лимфоцитов человека in vitro - Kolyvanova, S. S.; Solovyov, V. S.; Subbotin, A. M.; Kalyonova, L. F.; Narushko, M. V.; Колыванова, С. С.; Соловьёв, В. С.; Субботин, А. М.; Калёнова, Л. Ф.; Нарушко, М. В. (Tyumen State University Herald. Natural Resource Use and Ecology, 2016)
The effect of metabolites of 14 strains of the microorganisms isolated from the permafrost of West (near Tarko-Sale) and Eastern (Chara depression Chita Oblast) Siberia and Central Yakutia (Mamontova mountain) on the proliferative activity of peripheral blood lymphocytes (0(I)Rh+)) in the reaction of blast-cell transformation. The authors consider the number of blast-cell transformed lymphocytes in the spontaneous blast-cell transformation under the influence of mitogen for T-lymphocytes of phytohemagglutinin (PHA) and under microbial metabolites of permafrost of PHA + metabolites complex. It is found that different strains of the permafrost microorganisms can have both stimulatory and suppressive effect on lymphocyte proliferation. The strain F2 from Central Yakutia permafrost is exerting maximum stimulating effect (p<0.01), minimum – strains 9/48 (II) and 5/26 from Western Siberia permafrost (p <0.05). Strain F2 is increasing the level of lymphocyte proliferation in combination with PHA (p<0.05). Two strains of Western Siberia permafrost – 9/48 (II) and 3/07 (p<0.01 in both cases) and two strains of Eastern Siberia permafrost – 6/010 and 2/09 (p<0.01 in both cases) are significantly reducing PHA-stimulated lymphocyte proliferation. Исследовано влияние метаболитов 14 штаммов микроорганизмов (МО), выделенных из многолетнемерзлых пород (ММП) Западной (район Тарко-Сале) и Восточной (Чарская котловина Читинской области) Сибири и Центральной Якутии (Мамонтова гора), на пролиферативную активность лимфоцитов периферической крови (0(I)Rh+)) в реакции бласттрансформации (РБТЛ). Учитывалось число бласттрансформированных лимфоцитов в спонтанном варианте РБТЛ (с-РБТЛ); под влиянием митогена для Т-лимфоцитов фитогемагглютинина (ФГА); метаболитов МО из ММП; комплекса «ФГА+метаболиты». Установлено, что разные штаммы МО из ММП могут оказывать как стимулирующее, так и супрессивное влияние на пролиферацию лимфоцитов. Максимальное стимулирующее влияние оказал штамм F2 из ММП Центральной Якутии (p<0,01), минимальное – штаммы 9/48(II) и 5/26 из ММП Западной Сибири (p<0,05). Штамм F2 также способствовал увеличению уровня пролиферации лимфоцитов в комплексе с ФГА (p<0,05). Достоверно снижают стимулированную ФГА пролиферацию лимфоцитов 2 штамма из ММП Западной Сибири – 9/48(II) и 3/07 (p<0,01 в обоих случаях) и 2 штамма из ММП Восточной Сибири – 6/010 и 2/09 (p<0,01 в обоих случаях).